2011
DOI: 10.1017/s0029665111000577
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lifestyle intervention in overweight children

Abstract: Therapy of choice in obese children and adolescents is lifestyle intervention based on nutrition education, behavioural treatment and exercise treatment. Its efficacy even after the end of intervention has been proven by several randomised-controlled trials and meta-analyses including a recent Cochrane review. However, randomised-controlled trials are likely to overestimate the effectiveness. Studies under normal day-to-day circumstances demonstrated only a very moderate effect on weight loss (<10% success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 76 publications
2
53
1
8
Order By: Relevance
“…The success rate defined by reduction of BMI-SDS was 94% in the intervention group. Given the observed values of the difference and standard deviations of BMI-SDS change the power of this study was >0.999 at a random error level of 0.05 (Reinehr et al 2010c). …”
Section: Preliminary Findings Of the Intervention "Obeldicks Light"mentioning
confidence: 74%
See 4 more Smart Citations
“…The success rate defined by reduction of BMI-SDS was 94% in the intervention group. Given the observed values of the difference and standard deviations of BMI-SDS change the power of this study was >0.999 at a random error level of 0.05 (Reinehr et al 2010c). …”
Section: Preliminary Findings Of the Intervention "Obeldicks Light"mentioning
confidence: 74%
“…Our first preliminary findings may point towards an effectiveness of the new lifestyle intervention "Obeldicks light" for overweight children and adolescents as well as towards the usefulness of our study protocol and the accurateness of our study sample estimation (Reinehr et al 2010c): Our intervention and evaluation protocol was suitable for the participants of the study as demonstrated by a very low drop-out rate (3% in intervention and 16% in the control group). Furthermore, we have demonstrated in a previous study that our study population did not differ from a general population in Germany concerning social status or ethnicity (Finne et al 2009) also supporting the generalizability of our results and demonstrating that all social classes were addressed by our intervention.…”
Section: Preliminary Findings Of the Intervention "Obeldicks Light"mentioning
confidence: 75%
See 3 more Smart Citations